Film thickness and architecture effects in biaxially strained polymer supported Al/Mo bilayers. (June 2022) - Cordill, M.J.; Kreiml, P.; Putz, B.; Trost, C.O.W.; Lassnig, A.; Mitterer, C.; Faurie, D.; Renault, P.-O.
Abstract: Multilayers on polymer substrates are of interest for several technical applications. However, the true understanding of how one layer affects the other during mechanical loading is still unknown. In order to address this lack of knowledge, single and bilayer thin films of Al (250, 125, and 75 nm) and Mo (50 nm) were sputter deposited onto polyimide (PI, 50 µm) and biaxially strained in-situ with X-ray diffraction. The technique allows for the simultaneous measurement of lattice strains of Al and Mo to correlate the observed mechanical behavior of both materials. Using the evaluated film stress and full width at half maximum evolutions, four domains of mechanical behavior are identified. The presence of the domains in either Al or Mo depends on the thickness of the Al films and, more importantly, the bilayer architecture (Al/Mo/PI vs. Mo/Al/PI). Domain boundaries in Al were found to correspond well with domain boundaries in the Mo, such as necking in Al with fracture in Mo or simultaneous fracture in both materials. The maximum stress achieved in the Mo layers during biaxial straining was also found to highly depend on the architecture and depend less on the Al film thickness. Results will demonstrate that the film architecture (layer order) is more important than the film thickness to enhance fracture resistance. Graphical abstract: ga1 Highlights: Al/Mo bilayers on polyimide were strained in biaxial tension with in-situ XRD Domains designated by the stress and FWHM evolution to describe observed mechanisms Simultaneous observation of stress and FWHM response of Al and Mo films while loading Three bilayer architectures were investigated and four mechanical domains found Thin film architecture is as important as film thickness for fracture resistance